AGRIBUSINESS BRANDING: A SYSTEMATIC LITERATURE REVIEW FRAMEWORK - http://annals.feaa.usv.ro/index.php/annals/article/view/1406/1094; Smaranda Adina COSMA (USV Annals of Economics and Public Administration, 2022)
The economic, social and geopolitical context we are going through is characterized by an atypical dynamic, as complex as it is challenging. Companies are facing significant changes in production costs, access to raw materials and labor, financing opportunities and last but not least, consumer desires and needs. Brands and the relationship they have between the agribusiness stakeholders and the economic actors in the field (branding) have become a lait motive in the current economic reality. This topic is being discussed more and more often, the research being the link that could favor the rapid concretization of these increasingly indispensable tools. In this sense, measuring the contribution and at the same time the impact that the research on this topic have, is particularly important in shaping the new approach specific to global agribusiness. This paper aims to draw a theoretical perspective on the brand and its implications in agribusiness, respectively in other industries (non-agricultural and / or non-agri-food). This article is based on approaches to three very current topics: corporate social responsibility (CSR), sustainability, and valuesharing processes.